Small‐angle scattering contrast calculator for protein and nucleic acid complexes in solution. (10th November 2013) - Sarachan, Kathryn L.; Curtis, Joseph E.; Krueger, Susan
<x xml:space="preserve">Abstract</x> Small‐angle neutron scattering (SANS) with contrast variation can provide useful information about the structure and disposition of two or more chemically distinct components within a complex. The SASSIE Contrast Calculator (SCC) is a new software tool designed to assist in planning SANS experiments with contrast variation on protein and nucleic acid complexes. On the basis of the primary sequence and deuteration level of each protein or nucleic acid component, the SCC calculates and plots I(0), contrast and scattering length densities; since SANS experiments often complement small‐angle X‐ray scattering studies, the program provides both neutron and X‐ray parameters. The SCC is run as an integrated component of SASSIE [Curtis, Raghunandan, Nanda & Krueger (2012). Comput. Phys. Commun.183, 382–389], a software suite for atomistic modeling of ensembles of structures consistent with scattering data.